Lithium battery negative electrode material and preparation method thereof
By doping V elements into the SnO2 negative electrode material of lithium-ion batteries, and covering nitrogen-doped carbon nanowires on its surface and generating MnO2 nanosheets, the problem of volume expansion of SnO2 negative electrode material during charging and discharging is solved, which significantly improves the The battery cycle stability and rate performance are achieved.
Patent Information
- Application Number
- CN202411777960.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-05
- Publication Date
- 2025-02-18
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
The SnO2 negative electrode material used in lithium-ion batteries will expand in volume during charging and discharging, resulting in rapid capacity decay and poor circulation stability.
By doping V element into nanotin dioxide and coating nitrogen-doped carbon nanowires on the surface of SnO2-V composite material, finally, MnO2 nanosheets are generated through the reversible reaction of KMnO4 and carbon material, the multiplication of the negative electrode material is achieved. Time to cover.
The cycle performance and rate performance of the negative electrode material are improved, volume expansion is suppressed, conductivity and mechanical toughness are enhanced, and the cycle stability and capacity retention rate of the battery are significantly improved.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium battery negative electrode materials, and in particular to a lithium battery negative electrode material and a preparation method thereof. Background Art
[0002] Lithium-ion batteries are widely used in portable electronic devices such as mobile phones, laptops, tablet computers, and various electric vehicle fields due to their excellent properties such as high operating voltage, high energy density, environmental friendliness, and no memory effect. Lithium-ion batteries need to contain some basic materials to be able to work and supply power normally, such as positive electrode materials, negative electrode materials, diaphragm materials, and electrolyte substances. The physical and chemical properties of negative electrode materials have a significant impact on the electrochemical performance of lithium-ion batteries. Common negative electrode materials include carbon negative electrode materials, silicon negative electrode materials, tin negative electrode materials, and lithium titanate negative electrode materials. For example, SnO in tin negative electrode materials 2 are suitable negative electrode materials for lithium-ion batteries because they are relatively safe, have high energy density, and have large theoretical capacity. 2 Significant volume expansion occurs during charging and discharging, causing rapid capacity decay, thereby deteriorating the cycle stability of lithium-ion batteries.
[0003] For SnO 2 The shortcomings of the negative electrode material can be eliminated by combining it with carbon materials to suppress the volume change of the negative electrode material and improve the stability of the negative electrode material. However, the performance of the negative electrode material obtained by simply combining it with carbon materials is not enough to meet the demand. Therefore, it is necessary to develop new modification methods to further improve the electrochemical performance, cycle stability and rate capability of the negative electrode material. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a lithium battery negative electrode material and a preparation method thereof.
[0005] The purpose of the present invention can be achieved by the following technical solutions: A method for preparing a negative electrode material for a lithium battery comprises the following steps: Step S1: Mix tin dioxide and V powder in a ball mill tank, and then place them in a planetary ball mill for 10-15 hours. After the ball milling is completed, SnO 2 -V composite materials; Further, the mass ratio of tin dioxide to V powder is 0.7-1.4:0.05-0.1; Furthermore, the ball-to-material ratio in the planetary ball mill is 10:1, and the ball milling speed is 300-500 rpm.
[0006] Step S2: polyvinyl alcohol and zinc acetate dihydrate are stirred and mixed in deionized water, and then melamine is added, and the system temperature is controlled to be 20-30° C., and stirring is continued for 30 minutes, and then the mixed solution is spun into filaments under the action of electrostatics to obtain a carbon nanowire precursor; Further, the dosage ratio of polyvinyl alcohol, zinc acetate dihydrate, melamine and deionized water is 2-5 g: 1.5-3.5 g: 0.5-1.5 g: 30-50 mL; Furthermore, the conditions for electrospinning are: voltage 10-14 KV, needle diameter 0.5-1.5 mm, spinning distance 12-15 cm, temperature 20-30° C., humidity 40%-60%, and jet speed 0.03-0.05 mm / min.
[0007] Step S3: Mix the carbon nanowire precursor and SnO 2 -V composite material is added into the reactor and stirred and mixed evenly, then calcined at 160-260℃ for 1-2h, and then calcined at 900-1100℃ under argon for 3-5h, and cooled naturally to room temperature to obtain SnO 2 -V@N-MCNTs nanomaterials; Furthermore, the mass ratio of the carbon nanowire precursor to the nano-tin dioxide is 3-4:2.
[0008] Step S4: SnO 2 -V@N-MCNTs nanomaterials were added to a reactor containing deionized water and ultrasonically dispersed for 30 min. KMnO 4 Ultrasonication for 10-20 minutes, then heating the system to 50-60°C and stirring for reaction for 4-6 hours. After the reaction is completed, centrifugation, washing, and drying at 60°C for 6 hours to obtain a negative electrode material for a lithium battery; Furthermore, SnO 2 -V@N-MCNTs nanomaterials, KMnO 4 The dosage ratio of deionized water is 0.1-0.3g:0.25-0.8g:300mL.
[0009] The invention also discloses a lithium battery negative electrode material obtained by the preparation method.
[0010] Beneficial effects of the present invention: The lithium battery negative electrode material provided by the present invention uses relatively safe, high energy density, and large theoretical capacity tin dioxide as a substrate, and performs a modification process on it: firstly, V element is doped into nano tin dioxide by ball milling to improve the cycle performance of the negative electrode material; secondly, electrostatic spinning and high temperature calcination are combined to form SnO 2-V composite material surface coated with a layer of nitrogen-doped carbon nanowires, which increased the specific capacity of the matrix, inhibited the volume expansion of the negative electrode material during the charge and discharge process, and further improved the cycle stability; finally, the carbon material and KMnO 4 The reversible reaction generates MnO 2 Nanosheets are used to achieve secondary coating of negative electrode materials, thereby improving the rate performance of negative electrode materials.
[0011] The negative electrode material of the battery firstly uses ball milling to dope V powder into nano-tin dioxide, thereby improving the conductivity of nano-tin dioxide and reducing the impedance, thereby making Li + The mobility of Sn is improved, and the addition of V can effectively inhibit the agglomeration of Sn, thereby improving the cycle performance of the negative electrode material. Secondly, a mixture of polyvinyl alcohol, melamine, zinc acetate dihydrate and deionized water is electrospun to obtain a precursor of nitrogen-doped nanomaterials. When melamine is used as a nitrogen source for doping, the nitrogen element will produce pyrrole nitrogen and pyridinic nitrogen after high-temperature calcination in the subsequent steps. Pyrrole nitrogen and pyridinic nitrogen can increase active sites, thereby improving the lithium storage capacity. At the same time, the defects introduced after nitrogen doping provide more diffusion channels and more lithium storage space for lithium ions and electrolytes. Thirdly, the precursor and SnO 2 -V composite material is calcined and carbonized at high temperature to synthesize nitrogen-doped carbon nanowire-coated tin dioxide nanomaterial, which has excellent cycle performance. This is because the inactive substances generated by tin dioxide during the first charge and discharge process can inhibit volume expansion; the surface-coated carbon nanowires have good mechanical toughness and the pores in the structure can accommodate volume expansion, which can further improve the cycle stability of the nanomaterial. At the same time, the nanomaterial has a large surface area and a high porosity, which can shorten the Li + The diffusion path increases the electrochemical reaction active sites, and the pore space it contains can alleviate the Li + The huge volume change during the insertion and extraction process shows good rate performance; in addition, the coating of carbon nanowires also improves the conductivity of nanomaterials. 4 and SnO 2 -V@N-MCNTs nanomaterials surface carbon materials reversible reaction to generate MnO 2 Nanosheets, which realize secondary coating of nanomaterials, further increase the specific surface area of the negative electrode material, thereby increasing the contact area between the negative electrode material and the electrolyte. + The reaction with the internal tin dioxide increases, effectively increasing the Li + The migration rate of MnO increases, thereby improving the rate performance of the negative electrode material. 2 The formation of nanosheets is carried out by using carbon materials as reducing agents, which leads to the carbon materials and MnO 2The bonding interface of the nanosheets has a porous structure, which facilitates more electrolytes to enter the porous structure of the electrode material, thereby causing an increase in capacity during the cycle process. DETAILED DESCRIPTION
[0012] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example 1
[0013] A method for preparing a negative electrode material for a lithium battery comprises the following steps: Step S1: Mix tin dioxide and V powder in a ball mill tank, and then place them in a planetary ball mill for 10 hours. After the ball milling is completed, SnO 2 -V composite material, the mass ratio of tin dioxide and V powder is 0.7:0.05, the ball-to-material ratio in the planetary ball mill is 10:1, and the ball milling speed is 300rpm; Step S2: polyvinyl alcohol and zinc acetate dihydrate are stirred and mixed in deionized water, and then melamine is added, and the system temperature is controlled to 20°C, and stirring is continued for 30 minutes, and then the mixed solution is spun into filaments under the action of electrostatics to obtain a carbon nanowire precursor, the amount ratio of polyvinyl alcohol, zinc acetate dihydrate, melamine and deionized water is 2g:1.5g:0.5g:30mL, and the conditions for electrospinning are: voltage 10KV, needle diameter 0.5mm, spinning distance 12cm, temperature 20°C, humidity 40%, and injection speed 0.03mm / min; Step S3: Mix the carbon nanowire precursor and SnO 2 The -V composite material was added into the reactor and stirred and mixed evenly, and then calcined at 160°C for 1 h, and then calcined at 900°C under argon for 3 h, and then naturally cooled to room temperature to obtain SnO 2 -V@N-MCNTs nanomaterials, the mass ratio of carbon nanowire precursor and nano-tin dioxide is 3:2; Step S4: SnO 2 -V@N-MCNTs nanomaterials were added to a reactor containing deionized water and ultrasonically dispersed for 30 min. KMnO 4 Ultrasonication was performed for 10 min, and then the system was heated to 50 °C and stirred for 4 h. After the reaction was completed, centrifugation, washing, and drying at 60 °C for 6 h were performed to obtain the negative electrode material for lithium batteries, SnO 2 -V@N-MCNTs nanomaterials, KMnO 4The dosage ratio of deionized water is 0.1g:0.25g:300mL. Example 2
[0014] A method for preparing a negative electrode material for a lithium battery comprises the following steps: Step S1: Mix tin dioxide and V powder in a ball mill tank, and then place them in a planetary ball mill for 12 hours. After the ball milling is completed, SnO 2 -V composite material, the mass ratio of tin dioxide and V powder is 0.9:0.07, the ball-to-material ratio in the planetary ball mill is 10:1, and the ball milling speed is 300rpm; Step S2: polyvinyl alcohol and zinc acetate dihydrate are stirred and mixed in deionized water, and then melamine is added, and the system temperature is controlled to 25°C, and stirring is continued for 30 minutes, and then the mixed solution is spun into filaments under the action of electrostatics to obtain a carbon nanowire precursor, the amount ratio of polyvinyl alcohol, zinc acetate dihydrate, melamine and deionized water is 3g:2g:0.8g:30mL, and the conditions for electrospinning are: voltage 12KV, needle diameter 1mm, spinning distance 12cm, temperature 25°C, humidity 50%, and injection speed 0.04mm / min; Step S3: Mix the carbon nanowire precursor and SnO 2 The -V composite material was added into the reactor and stirred and mixed evenly, and then calcined at 190°C for 1.5 h, and then calcined at 1000°C under argon for 3 h, and then naturally cooled to room temperature to obtain SnO 2 -V@N-MCNTs nanomaterials, the mass ratio of carbon nanowire precursor and nano-tin dioxide is 3.5:2; Step S4: SnO 2 -V@N-MCNTs nanomaterials were added to a reactor containing deionized water and ultrasonically dispersed for 30 min. KMnO 4 Ultrasonication was performed for 10 min, and then the system was heated to 55 °C and stirred for 5 h. After the reaction was completed, centrifugation, washing, and drying at 60 °C for 6 h were performed to obtain the negative electrode material for lithium batteries, SnO 2 -V@N-MCNTs nanomaterials, KMnO 4 The dosage ratio of deionized water is 0.2g:0.5g:300mL. Example 3
[0015] A method for preparing a negative electrode material for a lithium battery comprises the following steps: Step S1: Mix tin dioxide and V powder in a ball mill tank, and then place them in a planetary ball mill for 13 hours. After the ball milling is completed, SnO 2-V composite material, the mass ratio of tin dioxide and V powder is 1.2:0.09, the ball-to-material ratio in the planetary ball mill is 10:1, and the ball milling speed is 400rpm; Step S2: polyvinyl alcohol and zinc acetate dihydrate are stirred and mixed in deionized water, and then melamine is added, and the system temperature is controlled to 30°C, and stirring is continued for 30 minutes, and then the mixed solution is spun into filaments under the action of electrostatics to obtain a carbon nanowire precursor, the amount ratio of polyvinyl alcohol, zinc acetate dihydrate, melamine and deionized water is 4g:3g:1g:40mL, and the conditions for electrospinning are: voltage 12KV, needle diameter 1mm, spinning distance 12cm, temperature 30°C, humidity 60%, and injection speed 0.05mm / min; Step S3: Mix the carbon nanowire precursor and SnO 2 The -V composite material was added into the reactor and stirred and mixed evenly, and then calcined at 230°C for 2h, and then calcined at 1100°C under argon for 5h, and then naturally cooled to room temperature to obtain SnO 2 -V@N-MCNTs nanomaterials, the mass ratio of carbon nanowire precursor and nano-tin dioxide is 4:2; Step S4: SnO 2 -V@N-MCNTs nanomaterials were added to a reactor containing deionized water and ultrasonically dispersed for 30 min. KMnO 4 Ultrasonication was performed for 20 min, and then the system was heated to 60 °C and stirred for 6 h. After the reaction was completed, centrifugation, washing, and drying at 60 °C for 6 h were obtained to obtain the negative electrode material for lithium batteries, SnO 2 -V@N-MCNTs nanomaterials, KMnO 4 The dosage ratio of deionized water is 0.25g:0.6g:300mL. Example 4
[0016] A method for preparing a negative electrode material for a lithium battery comprises the following steps: Step S1: Mix tin dioxide and V powder in a ball mill tank, and then place them in a planetary ball mill for 15 hours. After the ball milling is completed, SnO 2 -V composite material, the mass ratio of tin dioxide and V powder is 1.4:0.1, the ball-to-material ratio in the planetary ball mill is 10:1, and the ball milling speed is 500rpm; Step S2: polyvinyl alcohol and zinc acetate dihydrate are stirred and mixed in deionized water, and then melamine is added, and the system temperature is controlled to 30°C, and stirring is continued for 30 minutes, and then the mixed solution is spun into filaments under the action of electrostatics to obtain a carbon nanowire precursor, the amount ratio of polyvinyl alcohol, zinc acetate dihydrate, melamine and deionized water is 5g:3.5g:1.5g:50mL, and the conditions for electrospinning are: voltage 14KV, needle diameter 1.5mm, spinning distance 15cm, temperature 30°C, humidity 60%, and injection speed 0.05mm / min; Step S3: Mix the carbon nanowire precursor and SnO 2 The -V composite material was added into the reactor and stirred and mixed evenly, and then calcined at 260°C for 2 h, and then calcined at 1100°C under argon for 5 h, and then naturally cooled to room temperature to obtain SnO 2 -V@N-MCNTs nanomaterials, the mass ratio of carbon nanowire precursor and nano-tin dioxide is 4:2; Step S4: SnO 2 -V@N-MCNTs nanomaterials were added to a reactor containing deionized water and ultrasonically dispersed for 30 min. KMnO 4 Ultrasonication was performed for 20 min, and then the system was heated to 60 °C and stirred for 6 h. After the reaction was completed, centrifugation, washing, and drying at 60 °C for 6 h were obtained to obtain the negative electrode material for lithium batteries, SnO 2 -V@N-MCNTs nanomaterials, KMnO 4 The dosage ratio of deionized water is 0.3g:0.8g:300mL.
[0017] Comparative Example 1 The lithium battery negative electrode material in this comparative example is different from that in Example 4 in that V powder is not doped, and the rest are the same.
[0018] Comparative Example 2 The lithium battery negative electrode material in this comparative example is different from that in Example 4 in that the nitrogen-doped carbon nanowires are not coated, and is prepared by the following steps: Step A1: Mix tin dioxide and V powder in a ball mill tank, and then place them in a planetary ball mill for 15 hours. After the ball milling is completed, SnO 2 -V composite material, the mass ratio of tin dioxide and V powder is 1.4:0.1, the ball-to-material ratio in the planetary ball mill is 10:1, and the ball milling speed is 500rpm; Step A2: SnO 2 -V composite material and carbon powder were added into the reactor containing deionized water, ultrasonically dispersed for 30 min, and then KMnO 4Ultrasonication was performed for 10 min, and then the system was heated to 50 °C and stirred for 4 h. After the reaction was completed, centrifugation, washing, and drying at 60 °C for 6 h were performed to obtain the negative electrode material for lithium batteries, SnO 2 -V composite material, carbon powder, KMnO 4 The dosage ratio of deionized water is 0.3g:1g:0.8g:300mL.
[0019] Comparative Example 3 The lithium battery negative electrode material in this comparative example is different from that in Example 4 in that the surface of the negative electrode material is not coated with MnO 2 , and the rest are the same.
[0020] The negative electrode materials of lithium batteries prepared in Examples 1-4 and Comparative Examples 1-3 were mixed with acetylene black and sodium alginate in a ratio of 7:2:1 to prepare slurry, and coated to prepare negative electrode sheets; NCM811, acetylene carbon black and binder PVDF were mixed evenly in a mass ratio of 80:12:8, and coated on aluminum foil to prepare positive electrode materials; the separator was celgard2400, and the electrolyte was 1 mol / L LiPF 6 A lithium battery was prepared using a conductive salt and a solvent with a ratio of DMC:DEC:EC (wt%) of 1:1:1. The prepared lithium battery was tested for discharge specific capacity at the first charge and discharge at a charge and discharge cut-off voltage of 0.01 to 1.5 V and a charge and discharge rate of 0.1 C, and then the capacity retention rate after 100 cycles was tested. The test results are shown in the following table.
[0021] As can be seen from the above table, the first discharge specific capacity of the lithium battery negative electrode material prepared by the present invention is 1362-1418 mA·h / g, and the capacity retention rate after 100 cycles is ≥88.6%, indicating that the negative electrode material has excellent conductivity, cycle stability and small capacity loss after cyclic discharge, showing good application prospects.
[0022] The above contents are merely examples and explanations of the concept of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the scope defined by the concept of the invention, they should all fall within the protection scope of the present invention.
Claims
1. A method for preparing a negative electrode material for a lithium battery, characterized in that: The steps include: Step S1: mixing tin dioxide and V powder in a ball mill tank, and then placing them in a planetary ball mill for 10-15 hours. After the ball milling is completed, a SnO2-V composite material is obtained; Step S2: polyvinyl alcohol and zinc acetate dihydrate are stirred and mixed in deionized water, and then melamine is added, and the system temperature is controlled to be 20-30° C., and stirring is continued for 30 minutes, and then the mixed solution is spun into filaments under the action of electrostatics to obtain a carbon nanowire precursor; Step S3: adding the carbon nanowire precursor and the SnO2-V composite material into the reactor, stirring and mixing them evenly, calcining them at 160-260° C. for 1-2 hours, and then calcining them at 900-1100° C. under argon gas for 3-5 hours, and naturally cooling them to room temperature to obtain SnO2-V@N-MCNTs nanomaterials; Step S4: Add SnO2-V@N-MCNTs nanomaterials into a reactor containing deionized water, ultrasonically disperse for 30 minutes, then add KMnO4 and ultrasonically disperse for 10-20 minutes, then heat the system to 50-60°C and stir to react for 4-6 hours. After the reaction is completed, centrifuge, wash, and dry at 60°C for 6 hours to obtain the lithium battery negative electrode material.
2. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: In step S1, the mass ratio of tin dioxide to V powder is 0.7-1.4:0.05-0.
1.
3. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: In step S1, the ball-to-material ratio in the planetary ball mill is 10:1, and the ball milling speed is 300-500 rpm.
4. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: In step S2, the usage ratio of polyvinyl alcohol, zinc acetate dihydrate, melamine and deionized water is 2-5 g: 1.5-3.5 g: 0.5-1.5 g: 30-50 mL.
5. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: The conditions for electrospinning in step S2 are: voltage 10-14 KV, needle diameter 0.5-1.5 mm, spinning distance 12-15 cm, temperature 20-30° C., humidity 40%-60%, and jet speed 0.03-0.05 mm / min.
6. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: In step S3, the mass ratio of the carbon nanowire precursor to nano-tin dioxide is 3-4:
2.
7. The method for preparing a negative electrode material for a lithium battery according to claim 1, characterized in that: In step S4, the dosage ratio of SnO2-V@N-MCNTs nanomaterial, KMnO4 and deionized water is 0.1-0.3g: 0.25-0.8g: 300mL.
8. A negative electrode material for a lithium battery, characterized in that: The negative electrode material is prepared according to the method according to any one of claims 1-7.